Evaluating the association between DNM1L variants and Parkinson's disease in the Chinese population - Liu, Jiabin; Huang, Juanjuan; Zhao, Yuwen; Pan, Hongxu; Wang, Yige; Liu, Zhenhua; Xu, Qian; Sun, Qiying; Tan, Jieqiong; Yan, Xinxiang; Li, Jinchen; Tang, Beisha; et al. (Frontiers in Neurology, 2023)
Parkinson’s disease (PD) is a progressive movement disorder caused by a loss of dopaminergic neuron. Previous studies have highlighted the importance of mitochondria dynamics in the pathogenesis of PD. Dynamin-1-like (DNM1L) is a gene that encodes for dynamin-related protein 1 (DRP1), a GTPase essential for proper mitochondria fission. Here we evaluated the relationship between DNM1L variants and PD in the Chinese population. A total of 3879 PD patients and 2931 healthy controls were recruited and genotyped by whole-exome sequencing and whole-genome sequencing. As a result, we identified 23 rare variants in the coding region of DNM1L， while no difference in variant burden was shown between the cases and controls. We also identified 201 common variants in the coding and flanking regions and found two significant SNP, rs10844308 and rs143794289 (OR = 1.220 and 0.718, p = 0.025 and 0.036, respectively). We also performed a meta-analysis to correlate the two SNPs with PD risk. However, none of the common variants was significant using logistic regression. In conclusion, despite the critical role of DRP1, our study did not support the relationship between DNM1L variants and PD risk in the Chinese population.